Effects of Smoking on Hematological Parameters among Baghdad City - Mohammed, Wed Abbas (Darul Yasin Al Sys, 2025)
Cigarette smoking is widely recognized as a major risk factor in the development and progression of various chronic diseases, including atherosclerosis and chronic obstructive pulmonary disease. In Iraq, smoking remains prevalent across both rural and urban populations. It has been associated with significant alterations in inflammatory markers and hematological parameters. This study aimed to examine smoking habits and their effects on key blood parameters, including Total Leukocyte Count (TLC), Differential Leukocyte Count, Total Red Blood Cell Count (TRBC), Hemoglobin (Hb) concentration, and Packed Cell Volume (PCV). A total of 80 healthy adult males aged 20 to 56 years from Baghdad were enrolled, comprising 40 smokers and 40 non-smokers. Participant classification was based on a self-administered questionnaire. The results revealed that TLC, TRBC, Hb concentration, PCV, eosinophils, and lymphocytes were elevated in both light and heavy smokers compared to non-smokers, while neutrophil and monocyte levels were reduced. These findings suggest that cigarette smoking induces measurable changes in hematological profiles, which may contribute to its role in disease pathogenesis.